Potential of polarization/Raman lidar to separate fine dust, coarse dust, maritime, and anthropogenic aerosol profiles - Mamouri, Rodanthi-Elisavet; Ansmann, Albert (My University, 2017)
We applied the recently introduced polarization lidar-photometer networking (POLIPHON) technique for the first time to triple-wavelength polarization lidar measurements at 355, 532, and 1064 nm. The lidar observations were performed at Barbados during the Saharan Aerosol Long-Range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE) in the summer of 2014. The POLIPHON method comprises the traditional lidar technique to separate mineral dust and non-dust backscatter contributions and the new, extended approach to separate even the fine and coarse dust backscatter fractions. We show that the traditional and the advanced method are compatible and lead to a consistent set of dust and non-dust profiles at simplified, less complex aerosol layering and mixing conditions as is the case over the remote tropical Atlantic. To derive dust mass concentration profiles from the lidar observations, trustworthy extinction-to-volume conversion factors for fine, coarse, and total dust are needed and obtained from an updated, extended Aerosol Robotic Network sun photometer data analysis of the correlation between the fine, coarse and total dust volume concentration and the respective fine, coarse, and total dust extinction coefficient for all three laser wavelengths. Conversion factors (total volume to extinction) for pure marine aerosol conditions and continental anthropogenic aerosol situations are presented in addition. As a new feature of the POLIPHON data analysis, the Raman lidar method for particle extinction profiling is used to identify the aerosol type (marine or anthropogeni c) of the non-dust aerosol fraction. The full POLIPHON methodology was successfully applied to a SALTRACE case and the results are discussed. We conclude that the 532 nm polarization lidar technique has many advantages in comparison to 355 and 1064 nm polarization lidar approaches and leads to the most robust and accurate POLIPHON products.
Keywords: POLIPHON; Polarization lidar technique